1981
DOI: 10.1042/bj1950573
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan-collagen arrangements in developing rat tail tendon. An electron microscopical and biochemical investigation

Abstract: 1. Developing tail tendons from rats (19-day foetal to 126 days post partum) were examined by electron microscopy after staining for proteoglycan with a cationic copper phthalocyanin dye. Cuprolinic Blue, in a "critical electrolyte concentration" method. Hydroxyproline was measured on papain digests of tendons, from which glycosaminoglycuronans were isolated, characterized and quantified. 2. Mean collagen fibril diameters increased more than 10-fold with age according to a sigmoid curve, the rapid growth phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
136
0
5

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(155 citation statements)
references
References 21 publications
14
136
0
5
Order By: Relevance
“…Only recently, the fine structure of collagen fibrils has been better understood (41). The morphology of collagen fibers is characterized by a regular arrangement of fibrils tightly bundled together through GAGmediated proteoglycan interactions as shown in previous reports (15,39,42,43). We and others (24) have previously demonstrated the unique collagenase activity of catK, which is able to cleave at multiple sites within the triple helical region of tropocollagen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, the fine structure of collagen fibrils has been better understood (41). The morphology of collagen fibers is characterized by a regular arrangement of fibrils tightly bundled together through GAGmediated proteoglycan interactions as shown in previous reports (15,39,42,43). We and others (24) have previously demonstrated the unique collagenase activity of catK, which is able to cleave at multiple sites within the triple helical region of tropocollagen.…”
Section: Discussionmentioning
confidence: 99%
“…Proteoglycans consist of leucine-rich repeat core proteins such as biglycans, decorins, and fibromodulins with covalently attached glycosaminoglycan chains of dermatan sulfate (DS) (12,13), keratan sulfate (11), or chondroitin sulfate (14). These GAG chains are associated with nearby GAG chains through electrostatic interactions and build bridges between proteoglycan core proteins present on the collagen fibril surface (15). Several studies have shown that polysaccharide chains of these interfibrillar bridges are responsible for the mechanical integrity between collagen fibrils in connective tissues (16,17).…”
mentioning
confidence: 99%
“…Vibratome slices cut from glutaraldehyde-fixed material were incubated with 0.025% alcian blue at pH 5.7 in 0.025 M sodium acetate buffer containing 0.3 M MgCl 2 (15). Frozen sections from unfixed tissues were stained with 0.1% toluidine blue or 1% alcian blue at pH 1 (16).…”
Section: Methodsmentioning
confidence: 99%
“…We propose that during this second stage of fibril development the inhibition of the lateral growth of fibrils imposed by the hyaluronic acid is removed by the proportionate increase of chondroitin sulphate [34] and/or dermatan sulphate synthesised preferentially by the cells in response to their changing mechanical or microelectrical environment [35,36]. Chondroitin sulphate, unlike hyaluronic acid, establishes weak inonic interactions with collagen under physiological conditions.…”
Section: Hypothesismentioning
confidence: 99%